Pengaruh Transparansi, Akuntabilitas,, Partisipasi, Terhadap Kinerja Pengelolaan Dana Desa di Kecamatan Kutawaringin Kabupaten Bandung - Syakira Gusmi Manika; R. Budi Hendaris (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze the influence of Transparency, accountability, and participation on the performance of village fund management in villages in Kutawaringin District, Bandung Regency. The number of samples taken in this research was 55 village officials divided into 11 villages in Kutawaringin District, namely Buninagara, Cibodas, Cilame, Gajah Mekar, Jatisari, Jelegong, Kopo, Kutawaringin, Padasuka, Pameuntasan, Sukamulya. This research uses multiple linear regression data analysis methods. The results of the research indicate that partially transparency and accountability do not have a significant effect on the performance of village fund management, while participation has a positive and significant effect on the performance of village fund management. Simultaneously transparency, accountability, participation have a significant effect on village fund management in Kutawaringin District Village, Bandung Regency. The implications of this research indicate that active community participation contributes significantly more to the success of village fund management than simply implementing transparency and accountability. These findings emphasize the importance of a participatory approach at every stage of village fund management, from planning and implementation to evaluation of development programs. Therefore, village governments are advised to prioritize comprehensive community involvement to create more effective, responsive, and sustainable village fund management.